Effects of Salt Stress on Absorption And Distribution of Osmotic Ions in Wheat Seedlings (Bangladesh Journal of Botany, 2021)
Effects of salt stress on absorption and distribution of osmotic ions in wheat seedlings were studied with 4 winter wheat varieties under NaCl stress by exploring dynamic changes of Ca2+, K+, Na+, Ca2+/Na+, K+/Na+ and Na+ limiting ability. The results showed that the contents of K+, Ca2+ and the K+/Na+ ratio gradually decreased in a manner of both salt concentration dependent and stress time dependent. The extent of reduction of K+ and Ca2+ in root was much more severe than that in shoot. The ability of Na+ limiting in QM6 and DK961 was stronger than that in JM22 and QF1. These results indicate that the maintenance of higher Na+ content in root, Na+ limiting ability, Ca2+ and K+ concentration will be the main physiological traits for the salt-tolerance of wheat.Bangladesh J. Bot. 50(4): 1209-1214, 2021 (December)